The Experience of Novelty and the Novelty of Experience - Skavronskaya, Liubov; Moyle, Brent; Scott, Noel (Frontiers in Psychology, 2020)
In cognitive psychology novelty is an antecedent of attention, emotion, memory and behaviour. However, the relationship between novelty and experience memorability remains conceptually underdeveloped in tourism. This research applies cognitive appraisal theory to explore the contribution of novelty and emotion to memorable tourism experiences. Seventy-five (75) novel travel episodes were identified through semi-structured interviews. Analysis focused on the antecedent and consequent conditions of novelty. Novel experiences, whether positive or negative, were identified as critical to experience memorability. Novelty could be segmented into trip-related and event-related dimensions. Novelty contributes to how spatial, temporal and contextual details of tourism experiences are remembered and reconstructed due to the elicitation of intense emotions. Analysis revealed negative experiences deemed as novel were found to be re-evaluated and often remembered as a positive experience. A conceptual model titled ‘cognitive appraisal of novelty in memorable tourism experiences’ is presented for consideration in future research. By applying a retrospective and prospective approach the conceptual model explores the role of novelty through the process of cognitive appraisal, identifying goals, attention and prior experiences as central for the experience of novelty. Future research should consider the application of recent advance in cognitive appraisal theory to advance inquiry on tourism experiences as a psychological phenomenon.